GRAVIMETRIC MEASURMENTS IN EXTREMELY MOUNTAINOUS REGION OF THE TERRITORY OF SOUTH-WESTERN BULGARIARILA MOUNTAIN: GRAVIMETRIC MEASURMENTS IN EXTREMELY MOUNTAINOUS REGION OF THE TERRITORY OF SOUTH-WESTERN BULGARIARILA MOUNTAIN - Kirilova , Krasimira (JOURNAL SCIENTIFIC AND APPLIED RESEARCH, 2023)
The subject of the research is to perform gravimetric measurements in local extreme areas of the territory of South-western Bulgaria (S / W), and more precisely the north-western end of the Rila - Rhodope mountain massif - Rila mountain in order to analysis and evaluation the optimal option for practical modelling of the local geoid (quasi-geoid) in the area limited within the boundaries 41052’06"N<ϕ<42º21’22"N and 23001’11"E<λ<24º01’05"E. The measured force of gravity in 287 gravimetric points an evenly distributed on the study area provides reliable gravimetric information that helps to deduce the surface of the local geoid for the Rila Mountains, where topographic effects completely dominate the local variations of the gravitational field.